2009
DOI: 10.1371/journal.pntd.0000396
|View full text |Cite
|
Sign up to set email alerts
|

What Will Happen If We Do Nothing To Control Trachoma: Health Expectancies for Blinding Trachoma in Southern Sudan

Abstract: BackgroundUncontrolled trachoma is a leading cause of blindness. Current global trachoma burden summary measures are presented as disability adjusted life years but have limitations due to inconsistent methods and inadequate population-based data on trachomatous low vision and blindness. We aimed to describe more completely the burden of blinding trachoma in Southern Sudan using health expectancies.Methodology/Principal FindingsAge and gender specific trachomatous trichiasis (TT) prevalence was estimated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Recent surveys have found both extremely high prevalence of active trachoma (trachomatous inflammation-follicular (TF) and/or trachomatous inflammation-intense (TI)) and evidence of TT in children in some of the areas surveyed [25], [26]. These findings indicate that trachoma constitutes a major problem to public health in Southern Sudan [27]. However, not all of Southern Sudan is equally at risk, as indicated by recent surveys that identified areas where trachoma is not endemic [28].…”
Section: Introductionmentioning
confidence: 99%
“…Recent surveys have found both extremely high prevalence of active trachoma (trachomatous inflammation-follicular (TF) and/or trachomatous inflammation-intense (TI)) and evidence of TT in children in some of the areas surveyed [25], [26]. These findings indicate that trachoma constitutes a major problem to public health in Southern Sudan [27]. However, not all of Southern Sudan is equally at risk, as indicated by recent surveys that identified areas where trachoma is not endemic [28].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in Oman also found that females had a higher risk of trichiasis, which was attributed to barriers for trichiasis surgery [13]. In Sudan too women have been reported to live longer and suffer a longer duration of disabling trichiasis and visual disabilities compared with males [14]. Despite the decline in blinding trachoma in a country such as Oman, the gender gap might still be important and approaches need to be modified to bridge the gender gap.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed methods for the population based trachoma prevalence surveys have been described elsewhere [7] . In brief, surveys were conducted in ten districts in South Sudan between September 2001 and May 2005.…”
Section: Methodsmentioning
confidence: 99%
“…An ordinal logistic regression model to the observed VA data was used to explore the age and sex distribution of the three categories of vision status in participants with trichiasis: normal vision; low vision; and blindness. All participants in whom trichiasis and cataract was identified were excluded from analysis; however, it was not possible to adjust for visual impairment due to other causes such as refractive errors [9] , [10] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation